In-vivo fluorescence imaging of mice with principal component analysis - Ng, Yi Xiang. (2010)
In the field of optical imaging in small animals, engineers have adopted the use of activatable fluorescent and bioluminescent proteins to identify molecular targets or organs [1]. However, scientists have not been able to resolve the problem of poor resolution found in in-vivo optical imaging techniques for them to be used widely [2]. In this project, the author carried out a dynamic fluorescence molecular imaging method (DFMI) to map the anatomic locations of internal organs in living mice [3]. An inert dye named Indocyanine Green was injected and a series of images was taken right after the injection. By observing the distribution dynamics and the rate of metabolism of the dye at different locations, each organ could then be differentiated [2]. An analytical tool Principal Component Analysis was carried out to transform the temporal component of the data into spatial delineation of the organs. With this new non-invasive technique for carrying out organ identification, further developments can be made to improve accuracy and versatility in diagnosis of diseases and neurological disorders, or even identify tumours and develop innovative cancer treatments [4].